Experiences and Correlates of Violence Among American Indian and Alaska Native Youth: A Brief Report - Edwards, Katie M. (J Interpers Violence, 2020)
The purpose of this paper is to document the scope and correlates of past 6-month victimization among American Indian (AI) and Alaska Native (AN) youth. Types of victimization under investigation included sexual assault, dating violence, bullying, sharing of nude photos, sexual harassment, homophobic teasing, and racism. Participants were 400 AI and AN youth in grades 7–10 who completed a survey in school. Results documented concerning rates of all forms of victimization among AI and AN youth during the past 6 months. Although most forms of victimization were related, bullying (at school and electronically), racism, and sexual harassment occurred more often than sexual assault and dating violence. Older youth, girls, and sexual minorities were more likely to report some forms of violence than younger youth, boys, and heterosexual youth respectively. Compared to nonvictims, victim status was consistently related to depressive symptoms, suicidal ideation, and alcohol use and was less consistently correlated with feelings of school mattering. Evidence-based, culturally grounded prevention and response efforts are needed for AI and AN youth, as well as broader initiatives that seek to reduce health disparities among AI and AN youth.